2021
DOI: 10.1097/md.0000000000027116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between bone mineral density and the fracture of distal radius

Abstract: Low bone mineral density (BMD) was significantly related to the fracture of distal radius. Serum brain-derived neurotrophic factor (BDNF) level was closely related to BMD in spine and osteoporotic fractures. In this study, we aimed to explore the association of BDNF polymorphisms (rs6265 and rs7124442) with BMD and the fracture of distal radius. This retrospective study included 152 patients with distal radius fractures and 148 healthy controls. BDNF polymorphisms were detected via TaqMan allelic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Polymorphisms in the BDNF gene have been related to an increased risk of distal radius fractures and BMD. In a retrospective study of 152 participants with distal radius fractures and 148 control subjects, the BDNF polymorphism rs6265 increased the risk of osteoporosis and distal radius fractures [ 76 ].…”
Section: The Effect Of the Nervous System On Bonementioning
confidence: 99%
“…Polymorphisms in the BDNF gene have been related to an increased risk of distal radius fractures and BMD. In a retrospective study of 152 participants with distal radius fractures and 148 control subjects, the BDNF polymorphism rs6265 increased the risk of osteoporosis and distal radius fractures [ 76 ].…”
Section: The Effect Of the Nervous System On Bonementioning
confidence: 99%
“…Accordingly, an increased risk of falls is expected to be a risk factor for distal radial fractures [ 12 ]. DRF is one of the most common fractures caused by osteoporosis, and many studies have reported that low-energy trauma-induced DRF is associated with osteoporosis [ 13 , 14 , 15 , 16 ]. Distal radial fractures occur on average 15 years earlier than hip fractures [ 17 ].…”
Section: Introductionmentioning
confidence: 99%